Eight-Port Orthogonally Dual-Polarized Antenna Array for 5G Smartphone Applications - Li, Ming-Yang; Ban, Yong-Ling; Xu, Zi-Qiang; Wu, Gang; Sim, Chow-Yen-Desmond; Kang, Kai; Yu, Zhe-Feng (IEEE transactions on antennas and propagation, 2016)
A dual-polarized hybrid eight-antenna array operating in the 2.6-GHz band (2550-2650 MHz) for 5G communication multi-input multi-output (MIMO) operation in the smartphone is presented. The proposed hybrid antenna array elements are symmetrically placed along the long edges of the smartphone, and they are composed of two different four-antenna array types (C-shaped coupled-fed and L-shaped monopole slot) that exhibit orthogonal polarization. Therefore, coupling between the two antenna array types can be reduced, and the MIMO system performances are enhanced. A prototype of the proposed eight-antenna array is manufactured and measured. A good impedance matching (10 dB return loss or better), desirable cross-polarization discrimination (better than 15 dB), and an acceptable isolation (better than 12.5 dB) are obtained. Envelope correlation coefficient and channel capacity are also calculated to evaluate the MIMO performances of the proposed antenna array.